G457(P) Would some emergency admissions from children's accident and emergency be suitable for care in the community?. (27th April 2015) - Sutherby, J; Ewer, A; Clements, C; Lemer, C
Abstract : There has been a sharp increase in short-term paediatric admissions over the past decade. Not only is this costly, but could also be detrimental to the children's health; increasing the risk of hospital acquired infections and impacting on their psychological welfare. The Royal College of Nursing states that 'every child and young person has the right to expect care to be provided at home unless they need to be admitted to a hospital environment' (2009). The aim of this paper was to determine whether any patients either admitted from Children's A&E or invited to attend a Consultant/SpR led follow-up clinic would have been suitable for discharge and subsequent care at home by children's community nurses. Data was taken from emergency admissions from Children's A&E into the general paediatric ward for the period 1 st May to 30 th June 2014 (n = 114) and attendees to a Consultant/SpR led follow up clinic in paediatric A&E from 1 st June 2014 to 30 th June 2014 (n = 55). It was found that 13% of admissions audited would have been suitable for care in the community, equating to 15 patients (Figure 1 ). An additional 25 patients invited to the follow up clinic would have also been suitable for community care (Figure 2 ). The skills required from the CCN's were identified; medication administration, recording observations, reassuring and advising patients, performing investigations, changing dressings and relaying test results. This audit identified an unmet need and showed that the introduction of a CCN service could reduce the number of acute hospital admissions as well as decrease the number of children returning to an A&E review clinic.